Minimally Invasive Compared to Conventional Approach for Coronary Artery bypass Grafting Improves Outcome - Baishya, Jitumoni (Ann Card Anaesth, 2017)
INTRODUCTION: Minimally invasive (MI) cardiac surgery is a rapidly gaining popularity, globally as well as in India. We aimed to compare the outcome of MI to the conventional approach for coronary artery bypass graft (CABG) surgery. METHODS: This prospective, comparative study was conducted at a tertiary care cardiac surgical center. All patients who underwent CABG surgery via MI approach (MI group) from July 2015 to December 2015 were enrolled and were compared against same number of EuroSCORE II matched patients undergoing CABG through conventional mid-sternotomy approach (CON group). Demographic, intra- and post-operative variables were collected. RESULTS: In MI group, duration of the surgery was significantly longer (P = 0.029). Intraoperative blood loss lesser (P = 0.002), shorter duration of ventilation (P = 0.002), shorter Intensive Care Unit stay (P = 0.004), shorter hospital stay (P = 0.003), lesser postoperative analgesic requirements (P = 0.027), and lower visual analog scale scores on day of surgery (P = 0.032) and 1(st) postoperative day (P = 0.025). No significant difference in postoperative blood loss, blood transfusion, or duration of inotrope requirement observed. There was no conversion to mid-sternotomy in any patients, 8% of patients had desaturation intraoperatively. There was no operative mortality. CONCLUSION: MI surgery is associated with lesser intraoperative blood loss, better analgesia, and faster recovery.